USING WORD WALL FOR IMPROVING STUDENTSâ€™ WRITING â€œWHAT ARE YOU DOINGâ€ - Tiara Elyana; Setia Rini (Institut Keislaman Abdullah Faqih Gresik, 2021)
Abstract: The objectives of study is to investigate whether studentsâ€™ wrting skills is improved in using â€œwhat are you doingâ€ material through word wall as media of students of the eighth year at SMP Negeri 2 Sumowono. The difficulties to write sentences and developing ideas, poor understanding about grammar and lack of vocabulary, lack of interest in learning tenses made them confused as writing can be a means for creation mode in supporting, learning, or testing grammar structural concepts. Observation checklist and the test are used to get data of the research. The research results showed that the implementation of word wall was successful to improve progressively in eaach of the cycle I and the cycle II by knowing the passing grade, that is 70. The result of the mean of the pre-test in the cycle I is lower than the mean of the post-test.Â T-test result in cycle I is 13,899, in cycle 2 are 14,668. While the t-test in the cycle II is higher than the t-test of the cycle I. In conclusion, the writers can conclud that word wall can be used as media to improve the studentsâ€™ writing ability in â€œwhat are you doingâ€ at SMP Negeri 2 Sumowono.Keywords: Writing; Grammar; Word Wall; Media.